Pole piece and preparation method thereof, secondary battery, battery module, battery pack and power-consuming device

By setting the current collector, the first film layer and the second film layer in the electrode sheet and controlling the thickness relationship, the problem of curling during the cold pressing process of the electrode sheet is solved, and the processing efficiency and energy density of the secondary battery are improved.

CN115986126BActive Publication Date: 2025-03-07CONTEMPORARY AMPEREX TECHNOLOGY CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202111200094.3
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2021-10-14
Publication Date
2025-03-07
Estimated Expiration
2041-10-14

AI Technical Summary

Technical Problem

The existing pole sheets are prone to curling during cold pressing processing, which affects the processing performance, the energy density and processing efficiency of the secondary battery.

Method used

The structure of a current collector, a first film layer and a second film layer is adopted, wherein the first film layer comprises an electrode active material, the second film layer comprises a nanometal oxide ceramic material, and the thickness relationship of the first film layer, the second film layer and the current collector meets a specific range to avoid curling and improve the thickness and processing performance of the electrode sheet.

Benefits of technology

It effectively avoids the curling problem of the pole sheet during cold pressing processing, and at the same time makes the pole sheet have a smaller thickness, which improves the processing efficiency and volume energy density of the secondary battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN115986126B_ABST
    Figure CN115986126B_ABST
Patent Text Reader

Abstract

The present application provides a pole piece and a preparation method thereof, a secondary battery, a battery module, a battery pack and an electric device. The pole piece includes a current collector, a first film layer and a second film layer, the current collector is located between the first film layer and the second film layer, the first film layer includes an electrode active material, the second film layer includes a nano-metal oxide ceramic material, and the nano-metal oxide ceramic material includes at least one of nano-alumina and nano-zirconium oxide, wherein the thickness d0 of the current collector, the thickness d1 of the first film layer, and the thickness d2 of the second film layer satisfy 0.045≤d2 / (d0+d1)≤0.21, and optionally, 0.05≤d2 / (d0+d1)≤0.13.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of lithium batteries, and in particular to a pole piece and a preparation method thereof, a secondary battery, a battery module, a battery pack and an electrical device. Background Art

[0002] In recent years, with the application and development of various electronic products and new energy vehicles, the requirements for secondary batteries have become higher and higher. High energy density, flexible shape and size, high safety and low cost have become the inevitable trend of secondary battery development. Currently, one of the common means to improve the energy density and shape and size flexibility of secondary batteries is to reduce the thickness of secondary batteries.

[0003] One way to reduce the thickness of secondary batteries is to reduce the thickness of the pole piece. However, when manufacturing a pole piece with active material coated on one side, if the thickness of the pole piece is too small, it is easy to curl during the subsequent cold pressing process, thereby affecting the processing performance of the pole piece and further affecting the processing efficiency of the secondary battery. Therefore, the existing pole piece still needs to be improved. Summary of the invention

[0004] The present application is made in view of the above-mentioned problems, and its purpose is to provide a pole piece with a small thickness and good processing performance, so that the secondary battery has both high energy density and processing efficiency.

[0005] In order to achieve the above-mentioned objectives, the present application provides a pole piece and a preparation method thereof, a secondary battery, a battery module, a battery pack and an electrical device.

[0006] The first aspect of the present application provides a pole piece for an electrochemical cell, the pole piece comprising a current collector, a first film layer and a second film layer. The current collector is located between the first film layer and the second film layer. The first film layer comprises an electrode active material. The second film layer comprises a nano-metal oxide ceramic material, the nano-metal oxide ceramic material comprises at least one of nano-alumina and nano-zirconium oxide. The thickness d of the current collector is 0 , the thickness of the first film layer d 1 , the thickness of the second film layer d 2 Satisfy 0.045≤d 2 / (d 0 +d 1 )≤0.21. Optionally, the thickness of the current collector d 0 , the thickness of the first film layer d 1 , the thickness of the second film layer d 2 Satisfy 0.05≤d 2 / (d 0 +d 1)≤0.13. Thus, the current collector of the present application is provided with a first film layer containing active materials on one side, and a second film layer containing nano-metal oxide ceramic materials on the other side, and the thicknesses of the first film layer, the second film layer and the current collector satisfy a specific quantitative relationship. In this way, not only the problem of curling during cold pressing of the pole piece is solved, but also the pole piece has a smaller thickness, thereby improving the processing efficiency and volume energy density of the secondary battery.

[0007] In any embodiment of the present application, the thickness d of the second film layer 2 Optionally, the thickness d of the second film layer is 2 More preferably, the thickness d of the second film layer is 5 μm to 19 μm. 2 The thickness of the second film layer is controlled within a suitable range, which can further ensure the volume energy density of the secondary battery.

[0008] In any embodiment of the present application, the electrode is a negative electrode. The coating surface density of the first film layer is 110 g / m 2 ~150g / m 2 Optionally, the coating surface density of the first film layer is 125 g / m 2 ~150g / m 2 The compacted density of the first film layer is 1.4 g / cm 3 ~1.7g / cm 3 Optionally, the compaction density of the first film layer is 1.5 g / cm 3 ~1.7g / cm 3 The coating surface density and compaction density of the first film layer are controlled within a suitable range, so that the first film layer has a suitable thickness and a suitable content of negative electrode active material per unit volume, thereby improving the volume energy density and processing efficiency of the secondary battery.

[0009] In any embodiment of the present application, the current collector is selected from one of a metal foil and a composite current collector. Optionally, the current collector is a copper foil. The thickness d of the current collector is 0 The thickness of the copper foil is within the above range. Under the premise of avoiding curling during the cold pressing process of the pole piece, the second film layer can achieve a smaller thickness, thereby further saving the manufacturing cost of the secondary battery and improving the volume energy density of the secondary battery.

[0010] In any embodiment of the present application, the electrode is a positive electrode, and the coating surface density of the first film layer is 180g / m 2 ~250g / m 2 Optionally, the coating surface density of the first film layer is 200 g / m2 ~250g / m 2 The compacted density of the first film layer is 3.1 g / cm 3 ~3.7g / cm 3 Optionally, the compaction density of the first film layer is 3.5 g / cm 3 ~3.7g / cm 3 The coating surface density and compaction density of the first film layer are controlled within a suitable range, so that the first film layer has a suitable thickness and a suitable content of positive electrode active material per unit volume, thereby improving the volume energy density and processing efficiency of the secondary battery.

[0011] In any embodiment of the present application, the current collector is selected from one of a metal foil and a composite current collector, optionally an aluminum foil, and the thickness d of the current collector is 0 is 10 μm to 30 μm. Optionally, the thickness d of the current collector is 0 The thickness of the aluminum foil is within the above range. Under the premise of avoiding curling during the cold pressing process of the pole piece, the second film layer can achieve a smaller thickness, thereby further saving the manufacturing cost of the secondary battery and improving the volume energy density of the secondary battery.

[0012] In any embodiment of the present application, the nano metal oxide ceramic material includes nano aluminum oxide, and the mass percentage of the nano aluminum oxide is 50wt% to 100wt% based on the total mass of the nano metal oxide ceramic material. Optionally, the mass percentage of the nano aluminum oxide is 80wt% to 100wt%. More optionally, the mass percentage of the nano aluminum oxide is 100wt%. Controlling the mass percentage of the nano aluminum oxide in the second film layer within the above-mentioned appropriate range can enable the pole piece to have both good processing performance and low cost, thereby improving the processing efficiency of the secondary battery and reducing the manufacturing cost of the secondary battery.

[0013] In any embodiment of the present application, the second film layer is formed on the surface of the current collector by plasma arc spraying of the nano metal oxide ceramic material. The second film layer formed on the surface of the current collector by plasma arc spraying can improve the residual stress on the surface of the current collector without affecting the conductive properties of the current collector. In addition, the second film layer formed on the surface of the current collector by plasma arc spraying also has higher strength, hardness and toughness, which can greatly improve the processing performance of the pole piece, thereby improving the processing efficiency of the secondary battery.

[0014] In any embodiment of the present application, in the second film layer, the nano metal oxide ceramic material exists in the form of particles, and the average particle size of the particles is 20nm to 100nm. The average particle size of the nano metal oxide ceramic material particles is controlled within a suitable range, which is not only convenient for spraying, but also can improve the strength and toughness of the second film layer, thereby improving the processing performance of the pole piece, and further improving the processing efficiency of the secondary battery.

[0015] The second aspect of the present application also provides a method for preparing a pole piece, which includes steps S101 to S103.

[0016] S101, providing a current collector having a first film layer disposed on a single side, wherein the first film layer includes an electrode active material.

[0017] S102, a step for forming a second film layer, comprises spraying a nano metal oxide ceramic material on a surface of the current collector in a thickness direction where the first film layer is not provided, thereby forming the second film layer, wherein the nano metal oxide ceramic material comprises at least one of nano aluminum oxide and nano zirconium oxide.

[0018] S103, a step for preparing the pole piece, comprises cold pressing the pole piece after forming the second film layer, so as to obtain the pole piece.

[0019] Among them, in the pole piece, the thickness d of the current collector is 0 , the thickness of the first film layer d 1 , the thickness of the second film layer d 2 Satisfy 0.045≤d 2 / (d 0 +d 1 )≤0.21. Optionally, the thickness of the current collector d 0 , the thickness of the first film layer d 1 , the thickness of the second film layer d 2 Satisfy 0.05≤d 2 / (d 0 +d 1 )≤0.13. The pole piece prepared by the method is not only not easy to curl during cold pressing, but also has a small thickness, which can improve the processing efficiency and volume energy density of the secondary battery.

[0020] In any embodiment of the present application, the surface of the current collector in the thickness direction of which the first film layer is not provided is sprayed with a nano-metal oxide ceramic material, comprising:

[0021] The surface of the current collector in the thickness direction of the current collector itself where the first film layer is not provided is sprayed with nano metal oxide ceramic material by plasma arc spraying.

[0022] The second film layer formed on the surface of the current collector by plasma arc spraying can improve the residual stress on the surface of the current collector without affecting the conductive performance of the current collector. In addition, the second film layer formed on the surface of the current collector by plasma arc spraying also has higher strength, hardness and toughness, which can greatly improve the processing performance of the pole piece, thereby improving the processing efficiency of the secondary battery.

[0023] The third aspect of the present application also provides a method for preparing a pole piece, which includes steps S104 to S106.

[0024] S104, providing a current collector with a second film layer disposed on a single side, wherein the second film layer comprises a nano-metal oxide ceramic material, and the nano-metal oxide ceramic material comprises at least one of nano-aluminum oxide and nano-zirconium oxide.

[0025] S105, a step for forming a first film layer, comprising coating an electrode active material on a surface of the current collector in a thickness direction thereof where the second film layer is not provided, thereby forming the first film layer.

[0026] S106, a step for preparing the pole piece, comprising drying and cold pressing the pole piece after forming the first film layer, so as to obtain the pole piece.

[0027] Among them, in the pole piece, the thickness d of the current collector is 0 , the thickness of the first film layer d 1 , the thickness of the second film layer d 2 Satisfy 0.045≤d 2 / (d 0 +d 1 )≤0.21. Optionally, the thickness of the current collector d 0 , the thickness of the first film layer d 1 , the thickness of the second film layer d 2 Satisfy 0.05≤d 2 / (d 0 +d 1 )≤0.13.

[0028] The pole piece prepared by this method is not only not easy to curl during cold pressing, but also has a smaller thickness, which can improve the processing efficiency and volume energy density of the secondary battery.

[0029] In any embodiment of the present application, the current collector having a second film layer disposed on a single side includes:

[0030] The nano metal oxide ceramic material is sprayed on one surface of the current collector in the thickness direction thereof by plasma arc spraying, thereby obtaining the current collector with the second film layer disposed on one side.

[0031] The second film layer formed on the surface of the current collector by plasma arc spraying can improve the residual stress on the surface of the current collector without affecting the conductive performance of the current collector. In addition, the second film layer formed on the surface of the current collector by plasma arc spraying also has higher strength, hardness and toughness, which can greatly improve the processing performance of the pole piece, thereby improving the processing efficiency of the secondary battery.

[0032] The fourth aspect of the present application also provides a secondary battery, which includes the electrode sheet of the first aspect of the present application.

[0033] As a result, the secondary battery can have high volume energy density as well as high processing efficiency and low production cost.

[0034] In any embodiment of the present application, the secondary battery comprises at least one positive electrode sheet and at least one negative electrode sheet. The positive electrode sheet and the negative electrode sheet are arranged in sequence and spaced apart, and at least the outermost two electrode sheets of the positive electrode sheet and the negative electrode sheet are the electrode sheets of the first aspect of the present application.

[0035] A fifth aspect of the present application provides a battery module, comprising the secondary battery of the fourth aspect of the present application.

[0036] The sixth aspect of the present application provides a battery pack, comprising the battery module of the fifth aspect of the present application.

[0037] The seventh aspect of the present application provides an electrical device comprising at least one selected from the secondary battery of the fourth aspect of the present application, the battery module of the fifth aspect of the present application, or the battery pack of the sixth aspect of the present application.

[0038] The battery module, battery pack and electric device of the present application include the secondary battery provided by the present application, and thus have at least the same advantages as the secondary battery. BRIEF DESCRIPTION OF THE DRAWINGS

[0039] Figure 1 It is a schematic diagram of a pole piece according to one embodiment of the present application.

[0040] Figure 2 is a schematic diagram of a secondary battery according to one embodiment of the present application.

[0041] Figure 3 yes Figure 2 An exploded view of a secondary battery according to an embodiment of the present application is shown.

[0042] Figure 4is a schematic diagram of a battery module according to an embodiment of the present application.

[0043] Figure 5 It is a schematic diagram of a battery pack according to one embodiment of the present application.

[0044] Figure 6 yes Figure 5 An exploded view of a battery pack according to an embodiment of the present application is shown.

[0045] Figure 7 FIG. 1 is a schematic diagram of an electric device using a secondary battery according to an embodiment of the present application as a power source.

[0046] Description of reference numerals:

[0047] 10 pole piece; 11 current collector; 12 first film layer; 13 second film layer; 1 battery pack; 2 upper box; 3 lower box; 4 battery module; 5 secondary battery; 51 shell; 52 electrode assembly; 53 top cover assembly. DETAILED DESCRIPTION

[0048] Below, the embodiments of the electrode, secondary battery, battery module, battery pack and electrical device of the present application are specifically disclosed in detail with appropriate reference to the accompanying drawings. However, there are cases where unnecessary detailed descriptions are omitted. For example, there are cases where detailed descriptions of well-known matters and repeated descriptions of actually the same structure are omitted. This is to avoid the following description from becoming unnecessarily lengthy and to facilitate the understanding of those skilled in the art. In addition, the drawings and the following descriptions are provided for those skilled in the art to fully understand the present application and are not intended to limit the subject matter described in the claims.

[0049] "Scope" disclosed in the present application is limited in the form of lower limit and upper limit, and a given range is limited by selecting a lower limit and an upper limit, and the selected lower limit and upper limit define the boundary of a special range. The scope limited in this way can be including end values ​​or not including end values, and can be arbitrarily combined, that is, any lower limit can be combined with any upper limit to form a scope. For example, if the scope of 60-120 and 80-110 is listed for a specific parameter, it is understood that the scope of 60-110 and 80-120 is also expected. In addition, if the minimum range values ​​1 and 2 are listed, and if the maximum range values ​​3, 4 and 5 are listed, the following scope can be all expected: 1-3, 1-4, 1-5, 2-3, 2-4 and 2-5. In the present application, unless otherwise specified, the numerical range "ab" represents the abbreviation of any real number combination between a and b, wherein a and b are real numbers. For example, the numerical range "0-5" means that all real numbers between "0-5" are listed in this document, and "0-5" is just an abbreviation of these numerical combinations. In addition, when a parameter is expressed as an integer ≥ 2, it is equivalent to disclosing that the parameter is, for example, an integer of 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, etc.

[0050] Unless otherwise specified, all embodiments and optional embodiments of the present application can be combined with each other to form a new technical solution.

[0051] Unless otherwise specified, all technical features and optional technical features of this application can be combined with each other to form a new technical solution.

[0052] If there is no special explanation, all steps of the present application can be performed sequentially or randomly, preferably sequentially. For example, the method includes steps (a) and (b), which means that the method may include steps (a) and (b) performed sequentially, or may include steps (b) and (a) performed sequentially. For example, the method may further include step (c), which means that step (c) may be added to the method in any order. For example, the method may include steps (a), (b) and (c), or may include steps (a), (c) and (b), or may include steps (c), (a) and (b), etc.

[0053] If there is no special explanation, the "include" and "comprising" mentioned in this application are open-ended or closed-ended. For example, the "include" and "comprising" may mean that other components not listed may also be included or only the listed components may be included or only the listed components may be included.

[0054] If not specifically stated, in this application, the term "or" is inclusive. For example, the phrase "A or B" means "A, B, or both A and B". More specifically, any of the following conditions satisfies the condition "A or B": A is true (or exists) and B is false (or does not exist); A is false (or does not exist) and B is true (or exists); or both A and B are true (or exist).

[0055] Because metallic lithium has the advantages of light weight, low redox potential, and high energy density, it has become the most advantageous new green alternative energy source. In recent years, with the application and development of various electronic products and new energy vehicles and other industries, the requirements for secondary batteries have become increasingly higher. In some cases, in order to improve the energy density and shape and size flexibility of secondary batteries, lithium-ion secondary batteries need to be prepared into laminated batteries or thin secondary batteries, which requires the secondary batteries to have a smaller thickness.

[0056] One way to reduce the thickness of a secondary battery is to reduce the thickness of the pole piece. The pole piece of a secondary battery includes a current collector and an active material layer coated on the current collector. The current collector and the active material layer collect active ions generated by the electrochemical reaction through physical contact and conduct them to the external circuit, thereby realizing the mutual conversion of chemical energy and electrical energy.

[0057] For laminated batteries, if both sides of the current collector are coated with active materials, the active materials on one side cannot be used as active materials, which not only wastes active materials, but also limits the volume energy density of the secondary battery to a certain extent, affecting the battery capacity. Although coating the current collector with active materials on one side to prepare a pole piece can solve the above problems, the pole piece will curl during the cold pressing process due to uneven stress release on one side.

[0058] The inventors have found through research that one of the means to solve the problem of curling during the processing of pole pieces with single-sided active materials is to increase the thickness of the current collector. For conventional negative electrode current collectors, such as copper foil, when its thickness is increased to 25μm, the phenomenon of curling during the cold pressing process of the pole piece can be alleviated. For conventional positive electrode current collectors, such as aluminum foil, when its thickness is increased to 30μm, the phenomenon of curling during the cold pressing process of the pole piece can also be alleviated. However, although increasing the thickness of the current collector can alleviate the problem of curling during the processing of the pole piece to a certain extent, it also leads to a decrease in the volume energy density of the secondary battery.

[0059] The inventors have found through further research that setting a polymer coating, such as a polyester (PET) coating or a polypropylene (PP) coating, on the other side of the current collector coated with the active material can reduce the thickness of the pole piece while alleviating the problem of curling during the cold pressing process of the pole piece. However, compared with the technical solution of increasing the thickness of the current collector itself, setting a polymer coating can only reduce the thickness of the pole piece by a few microns, which has little effect on improving the volume energy density of the secondary battery.

[0060] In view of this, the inventors, after extensive experimental research, provide a pole piece for an electrochemical battery and a preparation method thereof, a secondary battery, a battery module, a battery pack and an electrical device.

[0061] Pole piece

[0062] like Figure 1 As shown, in the first aspect of the present application, a pole piece 10 for an electrochemical cell is proposed, the pole piece 10 comprises a current collector 11, a first film layer 12 and a second film layer 13. The current collector 11 is located between the first film layer 12 and the second film layer 13. The first film layer 12 comprises an electrode active material. The second film layer 13 comprises a nano-metal oxide ceramic material, wherein the nano-metal oxide ceramic material comprises at least one of nano-aluminum oxide and nano-zirconium oxide. The thickness d of the current collector 11 is 0 , the thickness d of the first film layer 12 1 , the thickness d of the second film layer 13 2 Satisfy 0.045≤d 2 / (d 0 +d 1 )≤0.21, optionally, the thickness d of the current collector 11 0 , the thickness d of the first film layer 12 1 , the thickness d of the second film layer 13 2 Satisfy 0.05≤d 2 / (d 0 +d 1 )≤0.20,0.05≤d 2 / (d 0 +d 1 )≤0.18,0.05≤d 2 / (d 0 +d 1 )≤0.15,0.05≤d 2 / (d 0 +d 1 )≤0.13,0.05≤d 2 / (d 0 +d 1 )≤0.12,0.06≤d 2 / (d 0 +d 1)≤0.12,0.06≤d 2 / (d 0 +d 1 )≤0.10,0.065≤d 2 / (d 0 +d 1 )≤0.095.

[0063] In the pole piece of the present application, the first film layer 12 and the second film layer 13 can be respectively arranged on opposite sides of the current collector 11 in the thickness direction thereof. The second film layer 13 can include one of nano-alumina and nano-zirconium oxide, or nano-alumina and nano-zirconium oxide mixed in any proportion. The thickness d of the first film layer 12 is 1 It can be understood as the width of the first film layer 12 along the thickness direction of the current collector 11. The thickness d of the second film layer 13 2 It can be understood as the width of the second film layer 13 along the thickness direction of the current collector 11 .

[0064] The above-mentioned nano-alumina and nano-zirconia can be nano-alumina ceramics and nano-zirconia ceramics sintered from nano-alumina and nano-zirconia powders. Among them, nano-alumina can be α-Al 2 O 3 The nano-zirconia can be nano-zirconia of any crystalline phase, for example, monoclinic, tetragonal, or cubic nano-zirconia. Optionally, the nano-zirconia is cubic c-ZrO 2 .

[0065] The second film layer 13 can be formed on the surface of the current collector by plasma arc spraying, thermal spraying, magnetron sputtering, etc., but is not limited thereto.

[0066] Although the mechanism is not yet clear, the inventors of the present application unexpectedly discovered that by arranging the first film layer and the second film layer on opposite sides in the thickness direction of the current collector itself, the first film layer can play the role of an active material layer while solving the problem of curling during cold pressing of the pole piece. The second film layer of the present application includes at least one of nano-alumina and nano-zirconium oxide. When the second film layer itself has a smaller thickness, the pole piece can have a greater hardness. In this way, not only can the problem of curling during cold pressing of the pole piece be avoided, but also the secondary battery can have a higher volume energy density. Not only that, because the above-mentioned nano-metal ceramic material is stable in nature and not easy to react with the electrolyte, the secondary battery can also maintain good electrochemical properties.

[0067] In addition, the inventors also found that, relative to the total thickness of the pole piece, the thickness of the first film layer is high, which means that the active material is relatively more, and the secondary battery can have a higher volume energy density; the thickness of the current collector is high, which means that the current collector has better conductivity and can fully exert the capacity of the secondary battery; the thickness of the second film layer is high, which means that the pole piece has higher strength, better deformation resistance and processing performance. In order for the secondary battery to exhibit high volume energy density, high capacity, suitable deformation resistance and processing performance, it is necessary to control the thickness of the first film layer, the current collector and the second film layer within a suitable range. It is not intended to be limited to any theory or explanation. The inventors found that the thickness of the first film layer, the current collector and the second film layer satisfies the above quantitative relationship, which can make the pole piece have a higher capacity and capacity utilization, and can also make the pole piece have suitable deformation resistance and processing performance. In this way, the volume energy density and processing efficiency of the secondary battery can be further improved.

[0068] In some embodiments, the thickness d of the second film layer 13 is 2 Optionally, the thickness d of the second film layer 13 may be ≥4 μm. 2 It can be 5μm~19μm, 5μm~15μm, 5μm~12μm, 5μm~10μm, 5μm~8μm, 6μm~8μm.

[0069] Without intending to be limited by any theory or explanation, the inventors have found that for single-sided coated secondary battery pole pieces, the thickness of the second film layer is within the above-mentioned suitable range, which can not only solve the problem of pole piece curling during the cold pressing process, but also make the pole piece have a smaller thickness, thereby further ensuring the volume energy density of the secondary battery.

[0070] In some embodiments, the electrode 10 may be a negative electrode. The coating surface density of the first film layer 12 may be 110 g / m 2 ~150g / m 2 Optionally, the coating surface density of the first film layer 12 is 115 g / m 2 ~150g / m 2 , 120g / m 2 ~150g / m 2 , 125g / m 2 ~150g / m 2 , 125g / m 2 ~145g / m 2 , 125g / m 2 ~140g / m 2 The compacted density of the first film layer 12 may be 1.4 g / cm 3 ~1.7g / cm 3 Optionally, the compaction density of the first film layer 12 is 1.45 g / cm3 ~1.7g / cm 3 , 1.5g / cm 3 ~1.7g / cm 3 , 1.5g / cm 3 ~1.68g / cm 3 , 1.5g / cm 3 ~1.65g / cm 3 .

[0071] The coating surface density of the first film layer is controlled within the above-mentioned appropriate range, which can reduce the stress released by the first film layer during the cold pressing process while ensuring the capacity of the secondary battery, thereby reducing the probability of curling of the pole piece. The compaction density of the first film layer is controlled within the above-mentioned appropriate range, which can make the negative electrode active material particles in the first film layer in close contact, increase the content of negative electrode active materials per unit volume, and thus improve the energy density of the battery. The first film layer has both appropriate coating surface density and compaction density, and can also make the first film layer have an appropriate thickness, so that the total thickness of the first film layer and the current collector is small. In this way, the problem of curling of the pole piece during the cold pressing process can be solved when the second film layer has a smaller thickness. The first film layer, the current collector, and the second film layer all have appropriate and smaller thicknesses, and the pole piece does not curl during the cold pressing process, which can improve the volume energy density and processing efficiency of the secondary battery.

[0072] In the negative electrode plate 10 of the present application, the current collector 11 may be a metal foil or a composite current collector. As an example of a metal foil, copper foil may be used. The composite current collector may include a polymer material base layer and a metal material layer formed on at least one surface of the polymer material base layer. As an example, the metal material may be selected from one or more of copper, copper alloy, nickel, nickel alloy, titanium, titanium alloy, silver, and silver alloy. As an example, the polymer material base layer may be selected from polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS), polyethylene (PE), etc.

[0073] In some embodiments, the current collector 11 may be a copper foil, and the thickness d of the current collector 11 is 0 Optionally, the thickness d of the current collector 11 may be 4.5 μm to 25 μm. 0 It is 4.5μm~23μm, 4.5μm~20μm, 4.5μm~18μm, 4.5μm~15μm, 4.5μm~12μm, 4.5μm~10μm, 4.5μm~8μm, 4.5μm~6μm.

[0074] The thickness of the copper foil as the current collector is controlled within a suitable range, which can ensure good conductivity on the one hand, and further reduce the thickness of the pole piece on the other hand, thereby improving the volume energy density of the secondary battery. In addition, the inventors found that when the thickness of the copper foil is within the above range, the second film layer can achieve a smaller thickness while avoiding curling during the cold pressing process of the pole piece, thereby further saving the manufacturing cost of the secondary battery and improving the volume energy density of the secondary battery.

[0075] In some embodiments, the electrode 10 may be a positive electrode. The coating surface density of the first film layer 12 may be 180 g / m 2 ~250g / m 2 Optionally, the coating surface density of the first film layer 12 is 185 g / m 2 ~250g / m 2 , 190g / m 2 ~250g / m 2 , 195g / m 2 ~250g / m 2 , 200g / m 2 ~250g / m 2 , 220g / m 2 ~250g / m 2 The compacted density of the first film layer 12 may be 3.1 g / cm 3 ~3.7g / cm 3 Optionally, the compaction density of the first film layer 12 is 3.2 g / cm 3 ~3.7g / cm 3 , 3.3g / cm 3 ~3.7g / cm 3 , 3.4g / cm 3 ~3.7g / cm 3 , 3.5g / cm 3 ~3.7g / cm 3 , 3.6g / cm 3 ~3.7g / cm 3 .

[0076] The coating surface density of the first film layer is controlled within the above-mentioned appropriate range, which can reduce the stress released by the first film layer during the cold pressing process while ensuring the capacity of the secondary battery, thereby reducing the degree of curling of the pole piece. The compaction density of the first film layer is controlled within the above-mentioned appropriate range, which can make the positive electrode active material particles in the first film layer in close contact, increase the content of positive electrode active materials per unit volume, and thus improve the energy density of the battery. The first film layer has both appropriate coating surface density and compaction density, and can also make the first film layer have an appropriate thickness, so that the total thickness of the first film layer and the current collector is small. In this way, the problem of pole piece curling during the cold pressing process can be solved when the second film layer has a smaller thickness. The first film layer, the current collector, and the second film layer all have appropriate and smaller thicknesses, and the pole piece does not curl during the cold pressing process, which can improve the volume energy density and processing efficiency of the secondary battery.

[0077] In the positive electrode plate 10 of the present application, the current collector 11 may be a metal foil or a composite current collector. As an example of a metal foil, the positive current collector may be an aluminum foil. The composite current collector may include a polymer material base layer and a metal material layer formed on at least one surface of the polymer material base layer. As an example, the metal material may be selected from one or more of aluminum, aluminum alloy, nickel, nickel alloy, titanium, titanium alloy, silver, and silver alloy. As an example, the polymer material base layer may be selected from polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS), polyethylene (PE), etc.

[0078] In some embodiments, the current collector 11 may be an aluminum foil, and the thickness d of the current collector 11 is 0 Optionally, the thickness d of the current collector 11 may be 10 μm to 30 μm. 0 It is 10μm~28μm, 10μm~25μm, 10μm~23μm, 10μm~20μm, 10μm~18μm, 10μm~15μm, 10μm~12μm.

[0079] The thickness of the aluminum foil as the current collector is controlled within a suitable range, which can ensure good conductivity and strength of the current collector on the one hand, and further reduce the thickness of the pole piece on the other hand, thereby improving the volume energy density of the secondary battery. In addition, the inventors found that when the thickness of the aluminum foil is within the above range, the second film layer can achieve a smaller thickness while avoiding curling during the cold pressing process of the pole piece, thereby further saving the manufacturing cost of the secondary battery and improving the volume energy density of the secondary battery.

[0080] In some embodiments, the nano metal oxide ceramic material may include nano alumina. Based on the total mass of the nano metal oxide ceramic material, the mass percentage of the nano alumina may be 50wt% to 100wt%. Optionally, the mass percentage of the nano alumina is 55wt% to 100wt%, 60wt% to 100wt%, 65wt% to 100wt%, 70wt% to 100wt%, 75wt% to 100wt%, 80wt% to 100wt%, 85wt% to 100wt%, 95wt% to 100wt%. More optionally, the mass percentage of the nano alumina is 100wt%.

[0081] The inventors found that nano-alumina can make the second film layer have the characteristics of high hardness and high strength, while nano-zirconia can make the second film layer have the characteristics of high toughness. Therefore, the second film layer composed of nano-alumina and nano-zirconia composite ceramic materials can have the characteristics of high hardness, high strength and high toughness. According to different requirements for the hardness and toughness of the pole piece, nano-alumina and nano-zirconia can be mixed in different proportions to prepare a second film layer with different mechanical properties. For solving the problem of curling of the pole piece during the cold pressing process, the main thing is to enhance the hardness of the pole piece, and compared with nano-zirconia, the cost of nano-alumina is lower. Therefore, controlling the mass percentage of nano-alumina in the second film layer within the above-mentioned higher range can make the pole piece have both good processing performance and lower cost, thereby improving the processing efficiency of the secondary battery and reducing the manufacturing cost of the secondary battery.

[0082] In some embodiments, the second film layer 13 may be formed by forming the nano-metal oxide ceramic material on the surface of the current collector by plasma arc spraying.

[0083] The inventors found that the second film layer formed on the surface of the current collector by plasma arc spraying can be attached to the surface of the current collector by mechanical bonding, and can improve the residual stress on the surface of the current collector without affecting the conductive performance of the current collector. In addition, the second film layer formed on the surface of the current collector by plasma arc spraying also has higher strength, hardness and toughness, which can greatly improve the processing performance of the pole piece, thereby improving the processing efficiency of the secondary battery.

[0084] As an example, the nano-metal oxide ceramic material is formed on the surface of the current collector by plasma arc spraying according to the following steps (1) to (5).

[0085] (1) A nano-metal oxide slurry is provided, wherein the nano-metal oxide is uniformly dispersed in deionized water.

[0086] (2) The step of preparing a mixed slurry comprises uniformly mixing the nano metal oxide slurry and the binder PVA to obtain a mixed slurry.

[0087] (3) The step of preparing nano-metal oxide particles comprises drying the mixed slurry by spray drying and then sieving to obtain nano-metal oxide particles of micron size.

[0088] (4) The step of preparing nano metal oxide ceramic powder comprises sintering the nano metal oxide particles at a certain sintering temperature for 5 to 15 minutes, cooling and grinding, thereby obtaining the nano metal oxide ceramic powder.

[0089] (5) The step of preparing the second film layer comprises heating the above-mentioned nano metal oxide ceramic powder to a molten state, and spraying it onto the current collector by plasma arc spraying, thereby forming the second film layer.

[0090] In the above step (4), the sintering temperature can be adjusted according to the type of nano metal oxide. For example, when the nano metal oxide is nano alumina, the sintering temperature can be 1100°C to 1280°C; when the nano metal oxide is nano zirconia, the sintering temperature can be 2500°C to 2800°C; when the nano metal oxide includes nano alumina and nano zirconia, nano alumina ceramic powder and nano zirconia ceramic powder can be prepared respectively according to steps (1) to (4), and then the two can be evenly mixed to prepare the second film layer.

[0091] It should be noted that the above example is only one implementation method of the second film layer of the present application, and the above example is intended to explain the present application rather than to limit the present application.

[0092] In some embodiments, in the second film layer, the nano metal oxide ceramic material may exist in the form of particles, and the average particle size of the particles may be 20nm~100nm, 20nm~90nm, 25nm~90nm, 30nm~85nm, 30nm~80nm, 30nm~70nm, 30nm~60nm, 40nm~60nm.

[0093] The average particle size of nano metal oxide ceramic material particles is controlled within a suitable range, which not only facilitates spraying, but also improves the strength and toughness of the second film layer, thereby improving the processing performance of the pole piece and further improving the processing efficiency of the secondary battery.

[0094] It should be noted that the membrane parameters given in this application, such as membrane thickness, compaction density and other ranges, all refer to the parameters of the membrane after cold pressing and compaction and used for assembling batteries.

[0095] In addition, the pole piece of the present application does not exclude other additional functional layers besides the film layer. For example, in some embodiments, the pole piece described in the present application may also include a conductive primer layer (e.g., composed of a conductive agent and a binder) disposed between the current collector film layers. In other embodiments, the pole piece of the present application also includes a covering protective layer covering the surface of the film layer.

[0096] In the present application, the thickness of the first film layer, the current collector and the second film layer have well-known meanings in the art and can be tested by methods known in the art, such as using a micrometer (such as Mitutoyo 293-100, with an accuracy of 0.1 μm).

[0097] In this application, the compaction density of the first film layer is a well-known meaning in the art and can be tested by methods known in the art. The compaction density of the first film layer = the coating surface density of the first film layer / the thickness of the first film layer. Among them, the surface density of the first film layer is a well-known meaning in the art and can be tested by methods known in the art. For example, take a single-sided coated and cold-pressed electrode and punch it into an area of ​​S 1 Weigh the small disc and record it as M 1 ; Then wipe off the first film layer of the pole piece after weighing, weigh the weight of the current collector, and record it as M 0 ; The surface density of the first film layer = (the weight of the pole piece M 1 - Weight of current collector M 0 ) / S 1 .

[0098] It should be noted that the above-mentioned various parameter tests on the membrane layer or the current collector can be conducted by sampling during the battery preparation process or by sampling from a prepared secondary battery.

[0099] The second aspect of the present application further provides a method for preparing a pole piece according to any embodiment of the first aspect of the present application. The method comprises steps S101 to S103.

[0100] S101, providing a current collector having a first film layer disposed on a single side, wherein the first film layer includes an electrode active material.

[0101] S102, a step for forming a second film layer, comprises spraying a nano metal oxide ceramic material on a surface of the current collector in a thickness direction where the first film layer is not provided, thereby forming the second film layer, wherein the nano metal oxide ceramic material comprises at least one of nano aluminum oxide and nano zirconium oxide.

[0102] S103, a step for preparing the pole piece, comprises cold pressing the pole piece after forming the second film layer, so as to obtain the pole piece.

[0103] Among them, in the pole piece, the thickness d of the current collector is 0 , the thickness of the first film layer d 1 , the thickness of the second film layer d 2 Satisfy 0.045≤d 2 / (d 0 +d 1 )≤0.21. Optionally, the thickness of the current collector d 0 , the thickness of the first film layer d 1 , the thickness of the second film layer d 2 Satisfy 0.05≤d 2 / (d 0 +d 1 )≤0.20,0.05≤d 2 / (d 0 +d 1 )≤0.18,0.05≤d 2 / (d 0 +d 1 )≤0.15,0.05≤d 2 / (d 0 +d 1 )≤0.13,0.05≤d 2 / (d 0 +d 1 )≤0.12,0.06≤d 2 / (d 0 +d 1 )≤0.12,0.06≤d 2 / (d 0 +d 1 )≤0.10,0.065≤d 2 / (d 0 +d 1 )≤0.095.

[0104] The pole piece prepared by this method is not only not easy to curl during cold pressing, but also has a smaller thickness, which can improve the processing efficiency and volume energy density of the secondary battery.

[0105] In some embodiments, the step of spraying the nano-metal oxide ceramic material on the surface of the current collector in the thickness direction of the current collector where the first film layer is not provided comprises:

[0106] The surface of the current collector in the thickness direction of the current collector itself where the first film layer is not provided is sprayed with nano metal oxide ceramic material by plasma arc spraying.

[0107] The second film layer formed on the surface of the current collector by plasma arc spraying can improve the residual stress on the surface of the current collector without affecting the conductive performance of the current collector. In addition, the second film layer formed on the surface of the current collector by plasma arc spraying also has higher strength, hardness and toughness, which can greatly improve the processing performance of the pole piece, thereby improving the processing efficiency of the secondary battery.

[0108] The third aspect of the present application also provides a method for preparing a pole piece, which includes steps S104 to S106.

[0109] S104, providing a current collector with a second film layer disposed on a single side, wherein the second film layer comprises a nano-metal oxide ceramic material, and the nano-metal oxide ceramic material comprises at least one of nano-aluminum oxide and nano-zirconium oxide.

[0110] S105, a step for forming a first film layer, comprising coating an electrode active material on a surface of the current collector in a thickness direction thereof where the second film layer is not provided, thereby forming the first film layer.

[0111] S106, a step for preparing the pole piece, comprising drying and cold pressing the pole piece after forming the first film layer, so as to obtain the pole piece.

[0112] Among them, in the pole piece, the thickness d of the current collector is 0 , the thickness of the first film layer d 1 , the thickness of the second film layer d 2 Satisfy 0.045≤d 2 / (d 0 +d 1 )≤0.21. Optionally, the thickness of the current collector d 0 , the thickness of the first film layer d 1 , the thickness of the second film layer d 2 Satisfy 0.05≤d 2 / (d 0 +d 1 )≤0.20,0.05≤d 2 / (d 0 +d 1 )≤0.18,0.05≤d 2 / (d 0 +d 1 )≤0.15,0.05≤d 2 / (d 0 +d 1 )≤0.13,0.05≤d 2 / (d 0 +d 1 )≤0.12,0.06≤d2 / (d 0 +d 1 )≤0.12,0.06≤d 2 / (d 0 +d 1 )≤0.10,0.065≤d 2 / (d 0 +d 1 )≤0.095. The pole piece prepared by the method is not only not easy to curl during cold pressing, but also has a small thickness, which can improve the processing efficiency and volume energy density of the secondary battery.

[0113] In some embodiments, providing a current collector with a second film layer disposed on a single side includes:

[0114] The nano metal oxide ceramic material is sprayed on one surface of the current collector in the thickness direction thereof by plasma arc spraying, thereby obtaining the current collector with the second film layer disposed on one side.

[0115] The second film layer formed on the surface of the current collector by plasma arc spraying can improve the residual stress on the surface of the current collector without affecting the conductive performance of the current collector. In addition, the second film layer formed on the surface of the current collector by plasma arc spraying also has higher strength, hardness and toughness, which can greatly improve the processing performance of the pole piece, thereby improving the processing efficiency of the secondary battery.

[0116] In addition, the secondary battery, battery module, battery pack, and electric device of the present application will be described below with reference to the drawings as appropriate.

[0117] In one embodiment of the present application, a secondary battery is provided.

[0118] Generally, a secondary battery includes a positive electrode sheet, a negative electrode sheet, an electrolyte and a separator. During the battery charging and discharging process, active ions are embedded and released back and forth between the positive electrode sheet and the negative electrode sheet. The electrolyte plays the role of conducting ions between the positive electrode sheet and the negative electrode sheet. The separator is set between the positive electrode sheet and the negative electrode sheet, mainly to prevent the positive and negative electrodes from short-circuiting, while allowing ions to pass through.

[0119] [Positive electrode]

[0120] The secondary battery of the present application includes at least one positive electrode sheet according to the first aspect of the present application, or a positive electrode sheet prepared according to the method of the second aspect or the third aspect of the present application.

[0121] In some embodiments, in the first film layer of the positive electrode sheet, the active material may be a positive electrode active material for a battery known in the art. As an example, the positive electrode active material may include at least one of the following materials: a lithium-containing phosphate with an olivine structure, a lithium transition metal oxide, and their respective modified compounds. However, the present application is not limited to these materials, and other traditional materials that can be used as positive electrode active materials for batteries may also be used. These positive electrode active materials may be used alone or in combination of two or more. Examples of lithium transition metal oxides may include, but are not limited to, lithium cobalt oxides (such as LiCoO 2 ), lithium nickel oxide (such as LiNiO 2 ), lithium manganese oxide (such as LiMnO 2 、LiMn 2 O 4 ), lithium nickel cobalt oxide, lithium manganese cobalt oxide, lithium nickel manganese oxide, lithium nickel cobalt manganese oxide (such as LiNi 1 / 3 Co 1 / 3 Mn 1 / 3 O 2 (Also referred to as NCM 333 )、LiNi 0.5 Co 0.2 Mn 0.3 O 2 (Also referred to as NCM 523 )、LiNi 0.5 Co 0.25 Mn 0.25 O 2 (Also referred to as NCM 211 )、LiNi 0.6 Co 0.2 Mn 0.2 O 2 (Also referred to as NCM 622 )、LiNi 0.8 Co 0.1 Mn 0.1 O 2 (Also referred to as NCM 811 ), lithium nickel cobalt aluminum oxide (such as LiNi 0.85 Co 0.15 Al 0.05 O 2 ) and its modified compounds, etc. Examples of lithium phosphates containing olivine structures may include, but are not limited to, lithium iron phosphate (such as LiFePO 4 (also referred to as LFP), composite materials of lithium iron phosphate and carbon, lithium manganese phosphate (such as LiMnPO 4 ), at least one of a composite material of lithium manganese phosphate and carbon, a composite material of lithium iron manganese phosphate, and a composite material of lithium iron manganese phosphate and carbon.

[0122] In some embodiments, the first film layer of the positive electrode sheet may further optionally include a binder. As an example, the binder may include at least one of polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), vinylidene fluoride-tetrafluoroethylene-propylene terpolymer, vinylidene fluoride-hexafluoropropylene-tetrafluoroethylene terpolymer, tetrafluoroethylene-hexafluoropropylene copolymer, and fluorine-containing acrylate resin.

[0123] In some embodiments, the first film layer of the positive electrode sheet may further optionally include a conductive agent, which may include, for example, at least one of superconducting carbon, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene, and carbon nanofibers.

[0124] In some embodiments, the positive electrode sheet can be prepared in the following manner: the components for preparing the first film layer, such as the positive electrode active material, the conductive agent, the binder and any other components, are dispersed in a solvent (such as N-methylpyrrolidone) to form a positive electrode slurry; the positive electrode slurry is coated on one surface of the positive electrode collector in the thickness direction, and after drying, the nano-metal oxide ceramic material is sprayed on the other surface of the positive electrode collector in the thickness direction, and then the positive electrode sheet is obtained after cold pressing and other processes; or, the nano-metal oxide ceramic material is first sprayed on one surface of the positive electrode collector in the thickness direction, and then the above-mentioned positive electrode slurry is coated on the other surface of the positive electrode collector in the thickness direction, and the positive electrode sheet is obtained after drying, cold pressing and other processes.

[0125] [Negative electrode]

[0126] The secondary battery of the present application includes at least one negative electrode sheet according to the first aspect of the present application, or a negative electrode sheet prepared according to the method of the second aspect or the third aspect of the present application.

[0127] In some embodiments, in the first film layer of the negative electrode sheet, the negative electrode active material may be a negative electrode active material for a battery known in the art. As an example, the negative electrode active material may include at least one of the following materials: artificial graphite, natural graphite, soft carbon, hard carbon, silicon-based materials, tin-based materials, lithium titanate, etc. The silicon-based material may be selected from at least one of elemental silicon, silicon oxide compounds, silicon-carbon composites, silicon-nitrogen composites, and silicon alloys. The tin-based material may be selected from at least one of elemental tin, tin oxide compounds, and tin alloys. However, the present application is not limited to these materials, and other traditional materials that can be used as negative electrode active materials for batteries may also be used. These negative electrode active materials may be used alone or in combination of two or more.

[0128] In some embodiments, the first film layer of the negative electrode plate may further include a binder. The binder may be selected from at least one of styrene-butadiene rubber (SBR), polyacrylic acid (PAA), sodium polyacrylate (PAAS), polyacrylamide (PAM), polyvinyl alcohol (PVA), sodium alginate (SA), polymethacrylic acid (PMAA) and carboxymethyl chitosan (CMCS).

[0129] In some embodiments, the first film layer of the negative electrode plate may further include a conductive agent, which may be selected from at least one of superconducting carbon, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene and carbon nanofibers.

[0130] In some embodiments, the first film layer of the negative electrode plate may optionally include other additives, such as a thickener (eg, sodium carboxymethyl cellulose (CMC-Na)).

[0131] In some embodiments, the negative electrode sheet can be prepared by the following method: the components for preparing the first film layer, such as the negative electrode active material, the conductive agent, the binder and any other components, are dispersed in a solvent (such as deionized water) to form a negative electrode slurry; the negative electrode slurry is coated on one surface of the negative electrode collector in the thickness direction, and after drying, the other surface of the negative electrode collector in the thickness direction is sprayed with nano-metal oxide ceramic material, and then cold pressing and other processes are performed to obtain the negative electrode sheet; or, the nano-metal oxide ceramic material is first sprayed on one surface of the negative electrode collector in the thickness direction, and then the above-mentioned negative electrode slurry is coated on the other surface of the negative electrode collector in the thickness direction, and after drying, cold pressing and other processes, the negative electrode sheet can be obtained.

[0132] [Electrolytes]

[0133] The electrolyte plays the role of conducting ions between the positive electrode and the negative electrode. The present application has no specific restrictions on the type of electrolyte, which can be selected according to needs. For example, the electrolyte can be liquid, gel or all-solid.

[0134] In some embodiments, the electrolyte is an electrolyte solution, which includes an electrolyte salt and a solvent.

[0135] In some embodiments, the electrolyte salt can be selected from at least one of lithium hexafluorophosphate, lithium tetrafluoroborate, lithium perchlorate, lithium hexafluoroarsenate, lithium bis(fluorosulfonyl)imide, lithium bis(trifluoromethanesulfonyl)imide, lithium trifluoromethanesulfonate, lithium difluorophosphate, lithium difluorooxalatoborate, lithium dioxalatoborate, lithium difluorodioxalatophosphate, and lithium tetrafluorooxalatophosphate.

[0136] In some embodiments, the solvent can be selected from at least one of ethylene carbonate, propylene carbonate, ethyl methyl carbonate, diethyl carbonate, dimethyl carbonate, dipropyl carbonate, methyl propyl carbonate, ethyl propyl carbonate, butylene carbonate, fluoroethylene carbonate, methyl formate, methyl acetate, ethyl acetate, propyl acetate, methyl propionate, ethyl propionate, propyl propionate, methyl butyrate, ethyl butyrate, 1,4-butyrolactone, cyclopentane sulfone, dimethyl sulfone, methyl ethyl sulfone and diethyl sulfone.

[0137] In some embodiments, the electrolyte may further include additives, such as negative electrode film-forming additives, positive electrode film-forming additives, and additives that can improve certain battery properties, such as additives that improve battery overcharge performance, additives that improve battery high or low temperature performance, etc.

[0138] [Isolation film]

[0139] In some embodiments, the secondary battery further includes a separator. The present application has no particular limitation on the type of separator, and any known porous separator with good chemical stability and mechanical stability can be selected.

[0140] In some embodiments, the material of the isolation membrane can be selected from at least one of glass fiber, non-woven fabric, polyethylene, polypropylene and polyvinylidene fluoride. The isolation membrane can be a single-layer film or a multi-layer composite film, without particular limitation. When the isolation membrane is a multi-layer composite film, the materials of each layer can be the same or different, without particular limitation.

[0141] In some embodiments, the positive electrode sheet, the negative electrode sheet, and the separator may be formed into an electrode assembly through a lamination process.

[0142] In some embodiments, the secondary battery may include an outer package, which may be used to encapsulate the electrode assembly and the electrolyte.

[0143] In some embodiments, the outer packaging of the secondary battery may be a hard shell, such as a hard plastic shell, an aluminum shell, a steel shell, etc. The outer packaging of the secondary battery may also be a soft package, such as a bag-type soft package. The material of the soft package may be plastic, and examples of the plastic include polypropylene, polybutylene terephthalate, and polybutylene succinate.

[0144] The present application has no particular restrictions on the number of positive electrode sheets and negative electrode sheets. In some embodiments, when the number of electrode sheets is greater than 3, the positive electrode sheets and the negative electrode sheets are arranged in sequence. Among the positive electrode sheets and the negative electrode sheets, at least the outermost two electrode sheets are the electrode sheets according to the first aspect of the present application, and the middle electrode sheet can be a electrode sheet coated with active materials on both sides.

[0145] The present application has no particular limitation on the shape of the secondary battery, which may be cylindrical, square or any other shape. Figure 2 The secondary battery 5 is a square structure as an example.

[0146] In some embodiments, reference Figure 3 , the outer packaging may include a shell 51 and a cover plate 53. Among them, the shell 51 may include a bottom plate and a side plate connected to the bottom plate, and the bottom plate and the side plate enclose a receiving cavity. The shell 51 has an opening connected to the receiving cavity, and the cover plate 53 can be covered on the opening to close the receiving cavity. The positive electrode sheet, the negative electrode sheet and the isolation membrane can form an electrode assembly 52 through a lamination process. The electrode assembly 52 is encapsulated in the receiving cavity. The electrolyte is infiltrated in the electrode assembly 52. ​​The number of electrode assemblies 52 contained in the secondary battery 5 can be one or more, and those skilled in the art can select according to specific actual needs.

[0147] In some embodiments, secondary batteries may be assembled into a battery module. The number of secondary batteries contained in the battery module may be one or more, and the specific number may be selected by those skilled in the art according to the application and capacity of the battery module.

[0148] Figure 4 4 is an example of a battery module. Figure 4 In the battery module 4, the plurality of secondary batteries 5 may be arranged in sequence along the length direction of the battery module 4. Of course, they may also be arranged in any other manner. Further, the plurality of secondary batteries 5 may be fixed by fasteners.

[0149] Optionally, the battery module 4 may further include a housing having a receiving space, and the plurality of secondary batteries 5 are received in the receiving space.

[0150] In some embodiments, the battery modules described above may also be assembled into a battery pack. The battery pack may contain one or more battery modules, and the specific number may be selected by those skilled in the art according to the application and capacity of the battery pack.

[0151] Figure 5 and Figure 6 1 is a battery pack 1 as an example. Figure 5 and Figure 6 The battery pack 1 may include a battery box and a plurality of battery modules 4 disposed in the battery box. The battery box includes an upper box body 2 and a lower box body 3. The upper box body 2 can cover the lower box body 3 and form a closed space for accommodating the battery modules 4. The plurality of battery modules 4 can be arranged in the battery box in any manner.

[0152] In addition, the present application also provides an electrical device, which includes at least one of the secondary battery, battery module, or battery pack provided in the present application. The secondary battery, battery module, or battery pack can be used as a power source for the electrical device, and can also be used as an energy storage unit for the electrical device. The electrical device may include mobile devices (such as mobile phones, laptops, etc.), electric vehicles (such as pure electric vehicles, hybrid electric vehicles, plug-in hybrid electric vehicles, electric bicycles, electric scooters, electric golf carts, electric trucks, etc.), electric trains, ships and satellites, energy storage systems, etc., but are not limited thereto.

[0153] As the electrical device, a secondary battery, a battery module or a battery pack may be selected according to its usage requirements.

[0154] Figure 7 The power consumption device is taken as an example. The power consumption device is a pure electric vehicle, a hybrid electric vehicle, or a plug-in hybrid electric vehicle. In order to meet the high power and high energy density requirements of the power consumption device for the secondary battery, a battery pack or a battery module can be used.

[0155] Another example of a device may be a mobile phone, a tablet computer, a notebook computer, etc. Such a device is usually required to be thin and light, and a secondary battery may be used as a power source.

[0156] Example

[0157] Hereinafter, the embodiments of the present application will be described. The embodiments described below are exemplary and are only used to explain the present application, and should not be construed as limiting the present application. If no specific techniques or conditions are indicated in the embodiments, the techniques or conditions described in the literature in this area or the product specifications are used. If the manufacturer is not indicated in the reagents or instruments used, they are all conventional products that can be obtained commercially.

[0158] Examples 1 to 20, Comparative Examples 2 to 4, Comparative Examples 9 to 10, Comparative Examples 12 to 13, Comparative Examples 15 to 16, Comparative Examples 18 to 28

[0159] Preparation of negative electrode

[0160] The negative electrode active material artificial graphite, the conductive agent acetylene black, the binder styrene butadiene rubber (SBR), and the thickener sodium carboxymethyl cellulose (CMC-Na) were dissolved in the solvent deionized water at a mass ratio of 95:2:2:1, and the mixture was fully stirred and mixed to prepare a negative electrode slurry; the negative electrode slurry was evenly coated on one surface of the negative electrode current collector copper foil, and a rectangular specimen of 49.5 mm*42 mm was obtained after drying and cutting;

[0161] Spraying a certain thickness of nano metal oxide ceramic material on the surface of the rectangular specimen not coated with the negative electrode active material in the thickness direction by plasma arc spraying;

[0162] The test piece is cold pressed at a cold pressing pressure of 50 to 130 T and a cold pressing speed of 20 to 80 m / min to obtain a negative electrode sheet.

[0163] Preparation of positive electrode

[0164] The positive electrode active material lithium iron phosphate, the binder polyvinylidene fluoride (PVDF), and the conductive agent acetylene black are dissolved in a solvent N-methylpyrrolidone (NMP) at a mass ratio of 97:2:1, and the mixture is fully stirred and mixed to obtain a positive electrode slurry; the positive electrode slurry is evenly coated on one surface of the positive electrode current collector aluminum foil, and a rectangular specimen of 49.5 mm*42 mm is obtained after drying and cutting;

[0165] Spraying a certain thickness of nano metal oxide ceramic material on the surface of the rectangular specimen not coated with the positive electrode active material in the thickness direction by plasma arc spraying;

[0166] The test piece is cold pressed at a cold pressing pressure of 50 to 130 T and a cold pressing speed of 20 to 80 m / min to obtain a positive electrode sheet.

[0167] For specific parameters, please see Tables 1 to 2.

[0168] Comparative Examples 1, 5-8, 11, 14, 17

[0169] The preparation method of the negative electrode sheet and the positive electrode sheet is the same as that of Example 1, except that the nano metal oxide ceramic material is not sprayed. Specific preparation parameters are shown in Tables 1-2.

[0170] Test Section

[0171] Pole curling test

[0172] At room temperature and pressure, the cold-pressed positive and negative pole pieces in Examples 1 to 20 and Comparative Examples 1 to 28 are placed on a flat table, and the distance between the flat table and the highest point of the pole piece is measured to be D. The degree of curling of the pole piece is measured by the size of D. When D>2.0cm, the degree of curling of the pole piece is high; when 2.0cm≥D>1.5cm, the degree of curling of the pole piece is medium-high; when 1.5cm≥D>0.8cm, the degree of curling of the pole piece is medium; when 0.8cm≥D>0.1cm, the degree of curling of the pole piece is medium-low; when 0.1cm≥D≥0cm, the degree of curling of the pole piece is not curled.

[0173] The test results of the pole pieces of the above-mentioned embodiments 1 to 20 and comparative examples 1 to 28 are shown in Tables 1 to 2.

[0174] Table 1: Negative electrode sheet parameters and test results of Examples 1 to 20 and Comparative Examples 1 to 28

[0175]

[0176]

[0177]

[0178] Table 2: Positive electrode sheet parameters and test results of Examples 1 to 20 and Comparative Examples 1 to 28

[0179]

[0180]

[0181] According to the test results of Comparative Examples 1-7, 20-28 and Examples 1-2, 15-20, it can be seen that coating the nano-metal oxide metal ceramic material on the other surface of the current collector coated with the electrode active material on one side can avoid curling during the cold pressing process of the pole piece while making the pole piece have a smaller thickness. In addition, 100wt% nano-alumina, 100wt% nano-zirconia, 50wt% nano-alumina + 50wt% nano-zirconia, 80wt% nano-alumina + 20wt% nano-zirconia have similar effects on solving the curling problem during the cold pressing process of the pole piece. Therefore, the appropriate nano-metal oxide ceramic material can be selected according to the requirements for production cost and mechanical properties of the pole piece.

[0182] In addition, according to the above results, Examples 1 to 20 have achieved good results. In contrast, Comparative Examples 1 to 28 have not achieved effective improvement in solving the problem of curling during the cold pressing process of the pole piece. It can be seen that a first film layer containing active materials is provided on one side of the current collector, and a second film layer containing nano-metal oxide ceramic materials is provided on the other side, and the thicknesses of the first film layer, the second film layer and the current collector meet a specific quantitative relationship, which can solve the problem of curling during the cold pressing process of the pole piece when the pole piece has a smaller thickness.

[0183] It should be noted that the present application is not limited to the above-mentioned embodiments. The above-mentioned embodiments are only examples, and the embodiments having the same structure as the technical idea and exerting the same effect within the scope of the technical solution of the present application are all included in the technical scope of the present application. In addition, without departing from the scope of the main purpose of the present application, various modifications that can be thought of by those skilled in the art to the embodiments and other methods of combining some of the constituent elements in the embodiments are also included in the scope of the present application.

Claims

1. A pole piece, characterized in that: It includes a current collector, a first film layer and a second film layer, the current collector is located between the first film layer and the second film layer, the first film layer includes an electrode active material, the second film layer includes a nano-metal oxide ceramic material, and the nano-metal oxide ceramic material includes at least one of nano-aluminum oxide and nano-zirconium oxide, wherein the thickness d0 of the current collector, the thickness d1 of the first film layer, and the thickness d2 of the second film layer satisfy 0.045≤d2 / (d0+d1)≤0.

21.

2. The pole piece according to claim 1, characterized in that: 0.05≤d2 / (d0+d1)≤0.

13.

3. The pole piece according to claim 1, characterized in that: The thickness d2 of the second film layer is ≥4 μm.

4. The pole piece according to claim 3, characterized in that: The thickness d2 of the second film layer is 5 μm to 19 μm.

5. The pole piece according to claim 4, characterized in that: The thickness d2 of the second film layer is 5 μm to 8 μm.

6. The pole piece according to claim 1, characterized in that: The electrode is a negative electrode, and the coating surface density of the first film layer is 110g / m 2 ~150g / m 2 The compaction density of the first film layer is 1.4 g / cm 3 ~1.7g / cm 3 .

7. The pole piece according to claim 6, characterized in that: The coating surface density of the first film layer is 125 g / m 2 ~150g / m 2 The compaction density of the first film layer is 1.5 g / cm 3 ~1.7g / cm 3 .

8. The pole piece according to claim 6, characterized in that: The current collector is selected from one of metal foil gold and a composite current collector, and a thickness d0 of the current collector is 4.5 μm to 25 μm.

9. The pole piece according to claim 8, characterized in that: The current collector is copper foil, and the thickness d0 of the current collector is 4.5 μm to 10 μm.

10. The pole piece according to claim 1, characterized in that: The pole piece is a positive pole piece, and the coating surface density of the first film layer is 180g / m 2 ~250g / m 2 The compaction density of the first film layer is 3.1 g / cm 3 ~3.7g / cm 3 .

11. The pole piece according to claim 10, characterized in that: The coating surface density of the first film layer is 200 g / m 2 ~250g / m 2 The compaction density of the first film layer is 3.5 g / cm 3 ~3.7g / cm 3 .

12. The pole piece according to claim 10, characterized in that: The current collector is selected from one of a metal foil and a composite current collector, and a thickness d0 of the current collector is 10 μm to 30 μm.

13. The pole piece according to claim 12, characterized in that: The current collector is aluminum foil, and the thickness d0 of the current collector is 10 μm to 15 μm.

14. The pole piece according to any one of claims 1 to 12, characterized in that: The nano metal oxide ceramic material comprises nano aluminum oxide. Based on the total mass of the nano metal oxide ceramic material, the mass percentage of the nano aluminum oxide is 50 wt % to 100 wt %.

15. The pole piece according to claim 13, characterized in that: The mass percentage of the nano-alumina is 80wt% to 100wt%.

16. The pole piece according to claim 15, characterized in that: The mass percentage of the nano-alumina is 100wt%.

17. The pole piece according to any one of claims 1 to 12, characterized in that: The second film layer is formed by forming the nano metal oxide ceramic material on the surface of the current collector by plasma arc spraying.

18. The pole piece according to any one of claims 1 to 12, characterized in that: In the second film layer, the nano metal oxide ceramic material exists in the form of particles, and the average particle size of the particles is 20nm to 100nm.

19. A method for preparing a pole piece, characterized in that: include: Providing a current collector having a first film layer disposed on a single side, wherein the first film layer comprises an electrode active material; The step of forming a second film layer comprises spraying a nano-metal oxide ceramic material on a surface of the current collector in a thickness direction where the first film layer is not provided, thereby forming the second film layer, wherein the nano-metal oxide ceramic material comprises at least one of nano-aluminum oxide and nano-zirconium oxide; The step of preparing the pole piece includes cold pressing the pole piece after forming the second film layer, thereby obtaining the pole piece, Among them, in the pole piece, the thickness d0 of the current collector, the thickness d1 of the first film layer, and the thickness d2 of the second film layer satisfy 0.045≤d2 / (d0+d1)≤0.

21.

20. The method according to claim 19, characterized in that The thickness d0 of the current collector, the thickness d1 of the first film layer, and the thickness d2 of the second film layer satisfy 0.05≤d2 / (d0+d1)≤0.

13.

21. The method according to claim 19, characterized in that The spraying of the nano-metal oxide ceramic material on the surface of the current collector in the thickness direction of the current collector itself where the first film layer is not provided comprises: The surface of the current collector in the thickness direction of the current collector itself where the first film layer is not provided is sprayed with nano metal oxide ceramic material by plasma arc spraying.

22. A method for preparing a pole piece, characterized in that: include: A current collector having a second film layer disposed on a single surface is provided, wherein the second film layer comprises a nano-metal oxide ceramic material, and the nano-metal oxide ceramic material comprises at least one of nano-aluminum oxide and nano-zirconium oxide; The step of forming a first film layer comprises coating an electrode active material on a surface of the current collector in a thickness direction thereof where the second film layer is not provided, thereby forming the first film layer; The step of preparing the pole piece includes drying and cold pressing the pole piece after forming the first film layer, thereby obtaining the pole piece. Among them, in the pole piece, the thickness d0 of the current collector, the thickness d1 of the first film layer, and the thickness d2 of the second film layer satisfy 0.045≤d2 / (d0+d1)≤0.

21.

23. The method according to claim 22, characterized in that The thickness d0 of the current collector, the thickness d1 of the first film layer, and the thickness d2 of the second film layer satisfy 0.05≤d2 / (d0+d1)≤0.

13.

24. The method according to claim 22, characterized in that The current collector provided with a second film layer on a single side includes: The nano metal oxide ceramic material is sprayed on one surface of the current collector in the thickness direction thereof by plasma arc spraying, thereby obtaining the current collector with the second film layer disposed on one side.

25. A secondary battery, characterized in that: It comprises a pole piece according to any one of claims 1 to 18, or a pole piece prepared according to the method according to any one of claims 19 to 24.

26. The secondary battery according to claim 25, characterized in that: The secondary battery comprises at least one positive electrode sheet and at least one negative electrode sheet, wherein the positive electrode sheets and the negative electrode sheets are arranged in sequence at intervals, and among the positive electrode sheets and the negative electrode sheets, at least the outermost two electrode sheets are the electrode sheets according to any one of claims 1 to 18, or the electrode sheets prepared by the method according to any one of claims 19 to 24.

27. A battery module, characterized in that: Includes the secondary battery according to claim 25 or 26.

28. A battery pack, characterized in that: Comprising the battery module as claimed in claim 27.

29. An electrical device, characterized in that: The battery comprises at least one selected from the secondary battery of claim 25 or 26, the battery module of claim 27, or the battery pack of claim 28.

Citation Information

Patent Citations

  • Lithium ion battery

    CN102637897A

  • Negative pole piece and lithium-ion battery

    CN105742613A